Clinicopathological and prognostic value of chemokine receptor CCR7 expression in head and neck squamous cell carcinoma: a systematic review and meta-analysis. Issue 4 (3rd April 2023) - Elmakaty, Ibrahim; Elsayed, Basel; Elmarasi, Mohamed; Kujan, Omar; Malki, Mohammed Imad
ABSTRACT: Objectives: This study aimed to identify the clinicopathological characteristics and prognostic value of CC chemokine receptor 7 (CCR7) expression in patients with head and neck squamous cell carcinoma (HNSSC). Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed in this meta-analysis. Up to the 2 nd of July 2022 a search was conducted using five databases: PubMed, Embase, Scopus, ProQuest, and Web of Science. The methodological standards for the epidemiological research scale were used to assess the quality of the included articles, and Stata software was used to synthesize the meta-analysis. Results: We considered 13 of the 615 studies which included 1005 HNSCC patients. High expression of CCR7 increased the pooled odds ratio (OR) of advanced stage, tumor size, metastasis and recurrence by 2.82 [95% confidence interval (CI) 1.84 to 4.33], 2.48 (95% CI 1.68, to 3.67), 3.57, 95% CI 2.25 to 5.05) and 3.93 (95% CI 2.03 to 7.64), respectively. High CCR7 reduced overall patient survival [hazard ratio 2.62 (95% CI 1.59 to 4.32)]. Conclusion: This study showed that high expression of CCR7 in HNSCC tumors was significantly associated with worse clinicopathological and survival outcomes, suggesting that CCR7 and its pathway could be potential therapeutic strategies for HNSCC.